A fluorescent chemosensor based on nonplanar donor-acceptor structure for highly sensitive and selective detection of picric acid in water. (August 2017) - Luo, Zijie; Liu, Bin; Si, Shufan; Lin, Yaojin; Luo, Crystal Shaojuan; Pan, Chengjun; Zhao, Chen; Wang, Lei
Abstract: Direct detection of picric acid in water samples is very important for social security and environmental protection. Herein, a novel donor-acceptor type fluorophore 3-(benzyloxy)-2-(4-(di-p-tolylamino)phenyl)-4 H -chromen-4-one has been designed, and synthesized. Due to its aggregation-induced emission enhancement characteristic, this fluorophore showed a very strong fluorescence in water. This fluorophore was then employed as highly sensitive chemosensor for picric acid, with a limit of detection of 370 nM in water. Moreover, this sensor showed very high selectivity towards picric acid among interfering nitroaromatics. At last, the sensing mechanism was carefully studied by using DFT computation and NMR spectra. This work provided a practical and reliable detection method for picric acid in water samples. Graphical abstract: Highlights: A novel highly emissive donor-acceptor flavonoid chemosensor was designed and successfully synthesized. The chemosensor achieved a fast and sensitive fluorescence response towards nitroaromatics, especially for picric acid in water samples. The sensing mechanism was studied via DFT calculation and NMR technique, suggesting the emission quenching may result from the photo-induced electron transfer between sensor molecule and picric acid.